Additive roles of platelets and fibrinogen in whole-blood fibrin clot formation upon dilution as assessed by thromboelastometry - Ninivaggi, Marisa; Feijge, Marion A. H.; Baaten, Constance C. F. M. J.; Kuiper, Gerhardus J. A. J. M.; Marcus, Marco A. E.; Cate, Hugo ten; Lancé, Marcus D.; Heemskerk, Johan W. M.; van der Meijden, Paola E. J. (Thrombosis and Haemostasis, 2014)
Blood dilution after transfusion fluids leads to diminished coagulant activity monitored by rotational thromboelastometry, assessing elastic fibrin clot formation, or by thrombin generation testing. We aimed to determine the contributions of blood cells (platelets, red blood cells) and plasma factors (fibrinogen, prothrombin complex concentrate) to fibrin clot formation under conditions of haemodilution in vitro or in vivo. Whole blood or plasma diluted in vitro was supplemented with platelets, red cells, fibrinogen or prothrombin complex concentrate (PCC). Thromboelastometry was measured in whole blood as well as plasma; thrombin generation was determined in parallel. Similar tests were performed with blood from 48 patients, obtained before and after massive fluid infusion during cardiothoracic surgery. Addition of platelets or fibrinogen, in additive and independent ways, reversed the impaired fibrin clot formation (thromboelastometry) in diluted whole blood. In contrast, supplementation of red blood cells or prothrombin complex concentrate was ineffective. Platelets and fibrinogen independently restored clot formation in diluted plasma, resulting in thromboelastometry curves approaching those in whole blood. In whole blood from patients undergoing dilution during surgery, elastic clot formation was determined by both the platelet count and the fibrinogen level. Thrombin generation in diluted (patient) plasma was not changed by fibrinogen, but improved markedly by prothrombin complex concentrate. In conclusion, in dilutional coagulopathy, platelets and fibrinogen, but not red blood cells or vitamin K-dependent coagulation factors, independently determine thromboelastometry parameters measured in whole blood and plasma. Clinical decisions for transfusion based on thromboelastometry should take into account the platelet concentration.
Keywords: Blood dilution; coagulation; fibrin clot formation; thrombin generation; platelets